Effect of hydrocolloids on physicochemical properties, stability, and digestibility of Pickering emulsions stabilized by nanofibrillated cellulose - Nuttinee Tangsrianugul (2022)
In this study, the effect of hydrocolloids with different electrostatic characteristics, namely negatively charged xanthan gum (XG), positively charged chitosan (CH), and non-ionic guar gum (GG), on the physicochemical properties, stability, and lipid digestibility of 10% (w/w) soybean oil-in-water Pickering emulsions stabilized by nanofibrillated cellulose (NFC) was investigated. Addition of XG and CH to the NFC-stabilized emulsions significantly increased the oil droplet sizes and apparent viscosity at high shear rates as compared with the addition of GG. The XG added emulsion showed the lowest rate and extent of creaming, whereas the CH added emulsion gave the highest extent of creaming. The addition of XG and CH led to a more pronounced effect on in vitro lipid digestion, i.e. changes in droplet sizes, surface charges, microstructure, and free fatty acid (FFA) release, than the addition of GG. The XG added emulsion showed the lowest rate and extent of lipid digestion possibly due to the high viscosity of the aqueous phase, large oil droplet sizes, and interaction of XG and calcium, resulting in the reduction of lipase activity. The CH added emulsion exhibited the highest extent of lipid digestion possibly due to binding between CH and FFAs and move away from the droplet surfaces, thereby facilitating the lipase activity. In summary, it can be concluded that ionic hydrocolloids exerted more influence on NFC-stabilized Pickering emulsions than non-ionic ones. These results may facilitate the design of highly stable emulsion-based functional food products with added hydrocolloids to promote health and wellness.